A home-based EEG neurofeedback treatment for chronic neuropathic pain—a pilot study - Mohamed Sakel; Christine A. Ozolins; Karen Saunders; Riya Biswas (Frontiers in Pain Research)
ObjectiveThis study assessed the effect of an 8-week home-based neurofeedback intervention in chronic neuropathic pain patients.Subjects/PatientsA cohort of eleven individuals with chronic neuropathic pain receiving treatment within the NHS framework.MethodsParticipants were trained to operate a home-based neurofeedback system. Each received a portable Axon system for one week of electroencephalogram (EEG) baselines, followed by an 8-week neurofeedback intervention, and subsequent 12 weeks of follow-up EEG baselines. Primary outcome measures included changes in the Brief Pain Inventory and Visual Analogue Pain Scale at post-intervention, and follow-ups compared with the baseline. Secondary outcomes included changes in depression, anxiety, stress, pain catastrophizing, central sensitization, sleep quality, and quality of life. EEG activities were monitored throughout the trial.ResultsSignificant improvements were noted in pain scores, with all participants experiencing overall pain reduction. Clinically significant pain improvement (≥30%) was reported by 5 participants (56%). Mood scores showed a significant decrease in depression (p < 0.05), and pain catastrophizing (p < 0.05) scores improved significantly at post-intervention, with continued improvement at the first-month follow-up.ConclusionThe findings indicate that an 8-week home-based neurofeedback intervention improved pain and psychological well-being in this sample of chronic neuropathic pain patients. A randomized controlled trial is required to replicate these results in a larger cohort. Clinical Trial Registration:https://clinicaltrials.gov/study/NCT05464199, identifier: (NCT05464199).